Aplikasi Pemandu Pencarian Wisata Terdekat Berbasis GIS Android Dengan Algoritma Dijkstra - Anam, Khairil; Hartono, Ony Dwi (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2019)
Sumenep Regency is one of the districts on Madura Island where the tourism sector is experiencing rapid development and improvement. Sumenep Regency has a natural and cultural tourist attraction, making it a destination for tourists. Not only is the attraction of the culture of his cow easy, but Sumenep Regency has a very beautiful natural attraction. The condition of natural tourism consists of natural scenery, high hills, beaches, high asta and diversity of marine potential. One of the popular tourist objects is Pantai Pantai Sembilan, Gili Labak Island and Gilii which have the best oxygen levels in the world. Tourists from outside the region, especially those who first visited Sumenep Regency will have a little difficulty in accessing tourist attractions in this city because they do not know in detail the information about the location of these tourist attractions. The purpose of this research is to build an Android-based Geographical Information System using the Dijkstra Algorithm, which is expected to help tourists from outside the Sumenep City area in displaying routes from one tourist spot to another. The method that is the basis for designing this GIS is the Graph Method, by applying the shortest route search algorithm, Dijkstra's Algorithm. The expected results with this application are that it can help, simplify, and accelerate tourists in finding and obtaining information about the location of tourist attractions in Sumenep Regency. Based on the closest travel search trials using the Android Application it produces an accuracy of 95%.